Exploring the efficacy of dialectical behaviour therapy and methylphenidate on emotional comorbid symptoms in adults with attention Deficit/Hyperactivity disorder: Results of the COMPAS multicentre randomised controlled trial - López-Pinar, Carlos; Selaskowski, Benjamin; Braun, Niclas; Fornés-Ferrer, Victoria; Euscher, Rebekka; Matthies, Swantje; Jans, Thomas; van Elst, Ludger Tebartz; Jacob, Christian; Huss, Michael; Sobanski, Esther; Retz, Wolfgang; et al. (Psychiatry research, 2023)
This study evaluated the efficacy of dialectical behaviour group therapy (GPT) vs. individual clinical management (CM) and methylphenidate (MPH) vs. placebo (PLB) on emotional symptoms in adults with ADHD. This longitudinal multicentre RCT compared four groups (GPT+MPH, GPT+PLB, CM+MPH, and CM+PLB) over five assessment periods, from baseline to week 130. Emotional symptomatology was assessed using SCL-90-R subscales. Of the 433 randomised participants, 371 remained for final analysis. At week 13, the GPT+MPH group showed smaller reductions in anxiety symptoms than the CM groups, but the differences disappeared at subsequent assessments. Improvements in emotional symptom were significantly predicted by reductions in core ADHD symptoms in all groups except the GPT+MPH group. The unexpected lack of between-group differences may be explained by a "floor effect", different intervention settings (group vs. individual), and psychotherapy type. Multiple regression analyses suggest a more specific effect of combined interventions (GPT+MPH). Implications for clinical practice are discussed. Clinical trial registration: ISRCTN54096201 (Current Controlled Trials).